2022
DOI: 10.1093/sleep/zsac318
|View full text |Cite
|
Sign up to set email alerts
|

Association between insomnia phenotypes and subclinical myocardial injury: the Multi-Ethnic Study of Atherosclerosis

Abstract: Study objectives To assess whether the association between insomnia and subclinical myocardial injury, as measured by cardiac troponin T (cTnT), differs across insomnia phenotypes. Methods We measured cTnT in 2188 participants in the Multi-Ethnic Study of Atherosclerosis (MESA) study who had completed sleep questionnaires and undergone unattended polysomnography (PSG) and 7-day actigraphy. Insomnia symptoms were defined as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…As shown in Figure 2, the ISSD phenotype has also been associated with specific adverse health outcomes in 37 studies: Cardiovascular (Bathgate et al, 2016; Bertisch et al, 2018; Fernandez‐Mendoza et al, 2012; Fernandez‐Mendoza et al, 2018; Hein et al, 2019a; Hein et al, 2019b; Huang et al, 2018; Nakazaki et al, 2012; Sigurdardottir et al, 2022; Vgontzas et al, 2009a). Metabolic (Castro‐Diehl et al, 2018; D'Aurea et al, 2015; Duan et al, 2023; Hein et al, 2018; Miner et al, 2022; Vasisht et al, 2013; Vgontzas et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2, the ISSD phenotype has also been associated with specific adverse health outcomes in 37 studies: Cardiovascular (Bathgate et al, 2016; Bertisch et al, 2018; Fernandez‐Mendoza et al, 2012; Fernandez‐Mendoza et al, 2018; Hein et al, 2019a; Hein et al, 2019b; Huang et al, 2018; Nakazaki et al, 2012; Sigurdardottir et al, 2022; Vgontzas et al, 2009a). Metabolic (Castro‐Diehl et al, 2018; D'Aurea et al, 2015; Duan et al, 2023; Hein et al, 2018; Miner et al, 2022; Vasisht et al, 2013; Vgontzas et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…• Cardiovascular (Bathgate et al, 2016;Bertisch et al, 2018;Fernandez-Mendoza et al, 2012;Fernandez-Mendoza et al, 2018;Hein et al, 2019a;Hein et al, 2019b;Huang et al, 2018;Nakazaki et al, 2012;Sigurdardottir et al, 2022;Vgontzas et al, 2009a).…”
Section: Night-time Sleep Durationunclassified
“…Several reasons might explain these divergent results. Differences in study populations, methodologies and definitions of insomnia can introduce variability [34]. Moreover, other confounding factors, such as lifestyle habits, comorbid conditions or medication usage, may not have been consistently accounted for across all studies.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the previously mentioned studies did not contain control groups that would allow for a direct comparison of our results. Our analysis of the existing literature found that PSG variables such as total sleep time (TST) and sleep efficiency were found to be different in certain groups of patients [ 16 , 45 , 46 ]. On the other hand, we did not observe these correlations in our study because these differences found in other research may influence group profiles such that they consist of only insomnia patients who were not present in our study.…”
Section: Discussionmentioning
confidence: 99%